Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Sukho Makmur Abadi Di Kabupaten Tangerang - Ayu Novitia Sari; Raden Yeti Sumiaty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Companies need Human Resources to manage and carry out their activities. Human Resources (HR) is one of the main things that regulates, analyzes and controls achievements within the company. For this reason, the position of humans as Human Resources (HR) is very important and is needed by every organization. The purpose of this study was to determine the effect of Motivation and Work Discipline on employee performance at PT Sukho Makmur Abadi both partially and simultaneously. The method used is quantitative method. The sampling technique used by the population is random sampling with a sample of 60 respondents. The results of this study are Motivation has a significant effect on Employee Performance with a correlation value of 0.584, a coefficient of determination of 0.330, hypothesis testing obtained t value> t table or (5,479> 2,001) thus H0 is rejected and H1 is accepted. Work Discipline has a significant effect on Employee Performance with a correlation value of 0.649, a coefficient of determination of 0.411, hypothesis testing obtained t value> t table or (6.489> 2.001) thus H0 is rejected and H1 is accepted. Motivation and Work Discipline have a significant effect on Employee Performance with the equation value Y = 2.053 + 0.447 (X1) + 0.520 (X2), correlation value of 0.710, coefficient of determination of 0.487, hypothesis testing obtained Fcount> Ftabel or (28.994> 3.160) thus H0 is accepted and H1 is accepted.